Morvan syndrome: a rare cause of syndrome of inappropriate antidiuretic hormone secretion - DEMIRBAS, SEREF (Clujul Med, 2017)
The syndrome of inappropriate antidiuretic hormone secretion (SIADH) accounts for an important part of hyponatremia cases. The causes of SIADH can be detected almost always. As a rare disorder, Morvan Syndrome can be defined by the sum of peripheral nerve hyperexcitability, autonomic instability and neuropsychiatric features. Antibodies to voltage-gated potassium channels (Anti – VGKC-Ab) including contactin associated protein-like 2 antibodies (CASPR2-Ab) and leucine-rich glioma inactivated protein 1 antibodies (LGI1-Ab) were previously known for the potential association with this condition. We present a Morvan Syndrome in a patient who presented with various neuropsychiatric symptoms and SIADH.